(untitled) (ENTHYMEMA, 2020)
After the skepticism that has long surrounded the notion of literary character, the so-called return to story-telling that has taken place in recent fiction has caused sharp criticism against modernist and postmodernist texts in which the human being is apparently reduced to an isolated fictional mind or is the produce of disconnected perceptions. Novels focusing on “the character who thinks” have thus incurred severe ethical or even moral criticism in that they represent humans as isolated subjects who are denied full development in the social context. This paper offers a different view by focusing on the monologizing character, who is emblematic of the fictional tradition under attack. After a theoretical reflection on particularities of this character, the paper dwells on two novels written in German: Peter Weiss’ Der Schatten des Körpers des Kutschers (1960) and Wolfgang Hildesheimer’s Tynset (1965). Specific attention is paid to the relationship that monologizing characters and monologue novels entertain with history.